Analysis Of The Placement And Needs Of General Cargo Ship Tanks With DWT 3650 Tons - Sade, Juswan (Maritime Park: Journal of Maritime Technology and Society, 2022)
The double bottom can enhance the ship's safety and a ballast tank. If the ship crashes into a rock and the outer bottom plate is torn, the watertight top tank will limit/protect the cargo from damage caused by water. The tank is a cargo storage container and is the central part of the liquid and gas transport vessel so that the cargo is maintained and safe. As a storage medium, the tank will always get a load from inside or outside the tank—calculating tank requirements using Simpson's approach. From the calculation results obtained fuel tank obtained 68,354 m3, and the diesel oil tank obtained 14,758 m3. The lubricating oil tank obtained 17,566 m3. The freshwater tank obtained 72,815 m3, and the Ballast tank obtained 356,098 m3.